The restoration of Ghirlandina Tower in Modena and the assessment of soil-structure interaction by means of dynamic identification techniques - Cadignani, Rossella, author.
1 online resource (x, 144 pages).
Keywords: This book is the first of a series of volumes on Built Heritage and Geotechnics, intended to reach a wide audience: professionals and academics in the fields of civil engineering, architecture, restoration and cultural heritage management, and even the wider public. The present volume provides essential information on the history of the construction of the Ghirlandina Tower in Modena, the techniques involved and the restoration works, and proves how the interaction with the supporting soil may explain the reasons behind the corrections that masons implemented during construction, the pattern of settlements suffered by the tower and the Cathedral and their mutual interaction. In addition to the above, there is one particular aspect that should capture the interest of a wide readership: in 1997 the Cathedral and the Ghirlandina Tower were included in the UNESCO World Heritage List, and it was recognized that the creation process shared by Lanfranco and Wiligelmo is a masterpiece of human creativity, in which a new dialectical relationship between architecture and sculpture was created in Romanesque art. The Modena complex bears exceptional witness to the cultural traditions of the 12th century in northern Italy's urban society, its organization, religious character, beliefs, and values all being reflected in the history of the buildings.